Awareness of privacy and data collection: exploring privacy policy effectiveness in Google Maps - Raibulet, Claudia; Wang, Kevin (Frontiers in Computer Science, 2025)
IntroductionConcerns over privacy and data collection have become increasingly important since software is everywhere. Apps such as Google Maps collect data on users' whereabouts, interests, habits, and more.MethodData collection practices are typically delivered through a privacy policy. To evaluate the effectiveness of privacy policies, we focus on Google Maps as a concrete and widely used app example. Our study explores user perspectives on privacy concerning the Google Maps app, and combines them with prior research to assess user awareness of data collection and privacy. To achieve our objective, we use a survey containing 19 questions (aligned with the themes explored in the state of the art, i.e., privacy policy awareness, users' habits regarding privacy, the effectiveness of privacy policies). The sampling strategy is a convenience one to receive the greatest number of responses. The received answers are analyzed by focusing on the readability and understandability of privacy policies.ResultsThe output indicates that privacy policies are complex, require a significant amount of time to be read, hard to understand by most of the users, and, hence, ignored by most of the users.DiscussionThe various reasons why privacy policies are ineffective and what causes users to avoid reading them are summarized and discussed. Potential solutions to the inefficacy of privacy policies are outlined and areas/hints for further research are revealed.